Efforts to Improve Collaboration Skills through the Team Games Tournament (TGT) Learning Model Assisted by Card Battle Media among Grade X (Phase E) Students at SMAN 3 Padang - Agustin, Putri Leony; Azhira, Azhira; Ardi, Ardi; Arsih, Fitri (Lombok Institute, 2025)
This classroom action research aimed to improve students' collaboration skills through the implementation of a cooperative learning model, specifically the Team Games Tournament (TGT) type, assisted by card battle media in class X E7 (Phase E) at SMAN 3 Padang. The study was conducted in September 2025 in two cycles; each Cycle consisted of planning, implementation of actions, observation, and reflection. The participants were 40 students in the 2025/2026 academic year. Collaboration skills were measured using an observation sheet developed based on collaboration indicators, including effective teamwork, adaptation among members, shared responsibility, deliberation and decision-making, and effective communication, and were supported by documentation and field notes. The results showed a consistent increase in students' collaboration skills across cycles: the baseline condition was 60.25%, which increased to 72.40% in Cycle I and reached 82.70% in Cycle II (collaborative category). Thus, the TGT model assisted by card battle media was proven effective in improving the collaboration skills of Grade X E7 students at SMAN 3 Padang.